Mangrove ecosystem conservation strategy againts tsunami threats at Holtekamp - John Dominggus Kalor; Baigo Hamuna (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2018)
Tsunami disaster has occurred in Jayapura coast for several times (1952, 1960, 1970, 1996, and the last one in 2011). The mangrove ecosystem, a natural fortress, is very strong against the Tsunami waves. This study aims to implement and develop a conservation program for mangrove ecosystems in which to prevent and minimize the impact of the Tsunami disaster in Youtefa Bay, Jayapura City. This research was conducted on 2-6 July 2018 at Holtekamp Teluk Yotefa, Jayapura. There were three main activities: (1) mapping locations prone to tsunamis in the Holtekamp coast, (2) FGD (3) declarating of mangrove conservation activities and evalution. The level of understanding of the Holtekamp Village community represented by 21 participants was obtained at the beginning of the activity 95.2% of the people who understood the importance of the mangrove ecosystem. As many as 85.7% of participants were committed and able to protect, planted and managed mangrove forests again to ensure the Holtekamp area is safe and free from tsunami threats. The observation result showed that the people of Holtekamp village were able to develop a system and prevent the impact of the tsunami disaster through the green lines of mangrove vegetation, as well as maintaining the integrity of the mangrove ecosystem in Youtefa Bay Jayapura.